The impact of utilizing educational games-based technology as learning media on students' numeration skills in high school economics subjects - Rahmat, Pupu Saeful; Jumantini, Entin; Suryani, Yeyen; Satriapraja, Novi; Suhenda, Enda (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This study was motivated by the low numeracy skills of students in economic subjects at SMA 2 Kuningan which was known through pre-research conducted. The purpose of this study was to determine the effect of using educational game-based technology learning media on students' numeracy skills in economic subjects in class XII SMAN 2 Kuningan Regency. The method used in this research is experimental method. The number of respondents in each class was 32 students each. Data processing methodology begins with instrument testing (including validity and reliability tests) followed by prerequisite assessment in the form of normality and homogeneity tests. Hypothesis testing using t-test and n-gain. Based on the results of hypothesis testing, there are significant differences in learning outcomes between students who utilize technology-based educational games and students who do not utilize technology-based educational games. These results indicate a difference in learning outcomes and numeracy skills between students who use technology-based educational games and those who do not. The results showed that the average normalized gain score of the experimental class of 76.76% was included in the effective category based on the interpretation of the effectiveness gain index. Therefore, it can be concluded that the integration of technology-based educational games is efficacious in improving students' numeracy skills in class XII economics subjects at SMAN 2 Kuningan